Knowledge, Practice, and Attitudes of Self-medication of Antibiotics among Medical and Nursing undergraduates of University of Colombo, Sri Lanka - Chathurika, J.N.; Darshika, P.G.K.; Kajipan, B.; Lakrandi, P.P.M.; Prabhani, S.D.D.; Sanjayath, K.; Thanuraj, T.; Wijayananda, P.T.A.; Nayanamali, M.A.A.; Menike, W.A.R.P. (University of Colombo, 2023)
Background: Antibiotic resistance is a worldwide emergency with a substantial healthcare and economic burden resulting in multi-drug resistant infections. Knowledge, attitude and practices of healthcare undergraduates can significantly influence antibiotic use as future healthcare professionals. Objective: To study Knowledge, Attitude, and Practices (KAP) of Self-Medication of Antibiotics (SMA) among medical and nursing undergraduates of the University of Colombo, Sri Lanka. Methods: A descriptive cross-sectional study was conducted from March 2022 to January 2023 among 401 nursing and medical undergraduates. Data was collected using a pre-designed self-administered questionnaire and was analyzed using SPSS version 26. A significant level was set as p<0.05 and results were presented in terms of descriptive statistics. Associations between demographics and KAP were defined in terms of Pearson’s chi-squared test. Mean comparisons of KAP between two faculties were performed using an independent sample t-test. Results: The study participants have a female majority (62.30%) aged 23-26 years (63.10%). Among the study subjects, only 19.10% of medical undergraduates and 23.30% of nursing undergraduates have good knowledge of SMA with a mean score of 9.79 (SD =2.10). Most participants (64.80%) have positive attitudes with a mean score of 7.71 (SD=1.69) and 64.58% have good practices toward SMA with a mean score of 8.45 (SD=2.28). Statistically significant associations were found between knowledge and the academic year (p=0.001) and age groups (p<0.001). Moreover, 46.1% have self-medicated themselves within the last year whereas Amoxicillin (15%) has the highest frequency. A significant association was identified between knowledge and practice of SMA (p<0.001) and between attitude and practice of SMA (p<0.001). Conclusion: Results showed that participants with good knowledge have significantly good practices of SMA. Participants with positive attitudes tend to follow good practices related to SMA. Despite having a good knowledge of antibiotics, the majority of the undergraduates have an average attitude regarding SMA which is not satisfactory in a healthcare-related undergraduate population.
Keywords: Antibiotic use; Attitude; Knowledge; Practice